2020
DOI: 10.2217/imt-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Antibody-Based Therapeutics: The Promise of Cancer Immunotherapy

Abstract: Antibody-based targeted therapies have been able to target cancers with enhanced specificity and high efficacy. In this regard, identifying cancer markers (antigens) that are only present (tumor-specific antigens) or have an increased expression (tumor-associated antigen) on the surface of cancer cells is a crucial step for targeted cancer treatment. Various cancer antigens have already been used for therapeutic and diagnostic purposes. MUC1 is one of the most important tumor markers with high levels of expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…Despite these advances, the detailed mechanisms by which MUC1 exerts its effects remain to be explored. Even though MUC1 vaccines and antibodies are being developed, with some having shown significant therapeutic effects and currently undergoing phase I/II clinical trials, certain side-effects and clinical safety issues need to be further explored and confirmed [ 3 , 109 , 110 ]. In conclusion, MUC1 is inextricably linked to various epithelial cancers, mandating further explorations of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, the detailed mechanisms by which MUC1 exerts its effects remain to be explored. Even though MUC1 vaccines and antibodies are being developed, with some having shown significant therapeutic effects and currently undergoing phase I/II clinical trials, certain side-effects and clinical safety issues need to be further explored and confirmed [ 3 , 109 , 110 ]. In conclusion, MUC1 is inextricably linked to various epithelial cancers, mandating further explorations of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…111 GGSK-1/30 is an anti-MUC1 IgG1 that exclusively targets tumor-associated MUC1 in the absence of any binding to fully glycosylated huMUC1 expressed on healthy epithelial cells. 65 It is demonstrated that GGSK-1/30 binds to breast cancer cells more strongly than commercially available mAbs SM3 and HMFG1. Recently, the exceptional specificity of GGSK-1/30 for hu(TA)MUC1 has allowed for the generation of an innovative diagnostic probe for the detection of hu(TA)MUC1 expressing breast tumors by conjugating this Ab with radioisotope 89 Zr.…”
Section: ■ Other Absmentioning
confidence: 99%
“…C595 (also known as NCRC48) is a murine IgG3 antibody that has been found to target MUC1 by binding to the RPAP motif within the protein core. 65 Radiolabeled conjugates of C595 have been applied for the diagnosis and therapy of MUC1-positive tumors. 76 In a clinical study by Kunkler et al 111 In-labeled Ab C595 was used for the immunoscintigraphy of patients with bladder tumors.…”
Section: ■ C595mentioning
confidence: 99%
See 2 more Smart Citations